Carbon Emission Disclosure: Testing The Influencing Factors - Denny Putri Hapsari; Nana Umdiana; Kodriyah; Nikke Yusnita Mahardini (CV. Inara, 2021)
This study aims to detremine the effect of profitability, leverage, company size and media exposure to carbon emission disclosure in manufacturing companies in the basic and chemical industry sectors in 2016 – 2018. The study population consisted of 71 companies and sampled as many as 13 companies or 39 data samples using a sampling technique that is purposive sampling. Data is collected by the company’s Annual Report or Sustainability Report and processed using SPSS version 25.Based on research results it can be concluded that : 1) there is no effect between profitability on carbon emission disclosure, 2) there is a influence between leverage on carbon emission disclosure, 3) there is no effect between company size on carbon emission disclosure, 4) there is a effect between media exposure on carbon emission disclosure .This study has limitations, including the limited observation period in 2016-2018 which allows it to give different results when the study period is longer.The expected benefit from the results of this research is that it can be used as a consideration in making investment decisions, considering that disclosure of information related to carbon emissions is one of the important things for stakeholders.